Approximating the impact of COVID-19 on regional production in countries with scarce subnational data. A proposal and application for Argentina during the first wave - Niembro, Andrés (2021)
In this paper we propose an index to approximate the territorial economic impact of the COVID-19 pandemic in contexts with scarce or outdated regional data, which is often the case in developing countries. This index is based on data that are usually available in most countries: a) the sectoral productive structure of the regions, b) the operational level of each sector, c) the mobility of workers in each region, and d) the possibility of remote work among sectors. The empirical application for Argentina describes the impact of the pandemic on regional production during the second and third quarters of 2020, both for the provinces and labor market areas. Our results show that the regional impact of COVID-19 on private economic activity was highly heterogeneous between and within provinces. The proposed index is also highly correlated with sporadic official data coming from national agencies, while it has a wider geographical and temporal scope, especially in terms of labor market areas.